The Norwegian-British-Swedish Antarctic Expedition. Science and politics - Domaas, Christel Misund; Drivenes, Einar-Arne; Bones, Stian (UiT Norges arktiske universitet, 2019)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; historie; internasjonal; klimaendringer; politikk; samarbeid; vitenskap

The Norwegian-British-Swedish Expedition (NBSX) to Antarctica 1949-52 - science and security - Lewander, Lisbeth (Berichte zur Polar- und Meeresforschung = Reports on Polar and Marine Research, 2007)
The most frequent way of summarizing the story of the NBSX may be illustrated by the following few paragraphs. Shortly after the Second World War had ended Norway took a leading role in organising the first international expedition to Antarctica. Norway was in charge of meteorology and surveying, Great Britain was responsible for geology and Sweden was entrusted with glaciology. The British RAF assisted in air operations 1949/50 with five officers (in finding a landing place for the expedition as well as for meteorological investigations, one officer remained as radio operator), the Norwegian Wideröe Company assisted in 1950/51 (air surveying) and the Swedish Air Force in 1951/52, with 6 officers (originally for reconnaissance of ice conditions as well as being prepared for emptying the base). The Norwegian sealer Norsel landed the party and the whaler Thorshövdi assisted as well for transport of dogs aircraft and weasels. For general overviews and details of the scientific achievements, logistics and perspectives of international cooperation there are several works available.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Note on occurence of limburgite in Dronning Maud Land, Antarctica - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1960, 1962)
The rocks from Dronning Maud Land, collected by T. LUNDE along 72° S and between 3° W and 7° E are mostly ordinary gneisses. However, a black, basaltic rock, apparently belonging to a sil! or a dyke has been found on Jutulsessen. The rock is lacking feidspar and consists only of augite, olivine, devitrified glass, and accessories. The chemical composition of the rock, mode and norm are given in table I. The present investigation shows that the Antarctic limburgite seems to be related to the normal olivine basalts, and not to the derivates of the basanite series.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi

Maudheim Revisited: The Morphology and Regime of the lce Shelf, 1950-1960 - Swithinbank, Charles (Norsk Polarinstitutt. Årbok 1960, 1962)
Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition, 1949-52, (71° 02' S, 10° 56' W) was revisited in January 1960 by the Norwegian Antarctic Expedition, 1956-60 under the leadership of SIGURD HELLF.. HELLE has very kindly made his observations available to me and has read the manuscript of this note. The work of his party gives a reliable measure of the accumulation of snow at Maudheim from 1952 to 1960 and allows a hetter estimate of the bottom melting on the ice shelf than was possible from the 1950-52 measurements. Air photographs taken in December 1958 by B. LuNCKE show the extent of changes in the ice front since 1951.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Basal metabolic rate of “tropical” man in a polar climate - Wilson, Ove (Biometeorology: Proceedings of the Second International Bioclimatological Congress Held at the Royal Society of Medicine, London, 4–10 Sept. 1960, Organized by "The International Society of Biometeorology", 1962)
Naked man in his mode of heat regulation can be regarded as a tropical or subtropical creature with a narrow zone of adaptability, and the difference in the BMR determined in the tropics and in a temperate zone for the same individuals does not seem to exceed 10 per cent. In the climatic extremes he raises his calorific output in situations of stress but does not adapt by further changing his BMR. Some native people, however, appear to have the ability to endure a moderate cold stress without increasing their heat production above normal basal values. The metabolic determinations made by the author on the Norwegian—British–Swedish Expedition during 2 years of continuous exposure to the Antarctic climate show that there is no difference in the mean level of the BMR of white man whether he lives in a temperate or a polar climate. Other studies in cold regions support this view. Evidence of acclimatization of man to cold will not be found in the basal metabolic rate. However, the author's investigations show that the polar climate in its extreme form, as it is encountered by man in the Antarctic, can impose certain seasonal variations in the BMR. This periodicity in BMR is probably not a direct effect of climate on metabolism, but is related to it by reason of the typical activity pattern which ensues in the Antarctic climate. In agreement are the seasonal changes in BMR in the Arctic reported by Russian workers. The preliminary results of Lewis and Masterton in North Greenland, on the other hand, do not indicate a consistent seasonal variation. In changing from a temperate to a tropical climate, the BMR may vary within a narrow range of about 10 per cent, decreasing in the hot environment, but not all persons will show such a change. The seasonal variation found by the author in a polar climate is almost of the same order as the change in the tropics. It may be that the alterations in BMR caused by a change to a tropical climate are due to similar influences, which, however, do not exhibit the same seasonal incidence, because of the uniformity of the climate the year around. This implies that the basal metabolism of white man is essentially the same in all climates, but varies within a narrow range, not as a direct result of climate itself or its mean temperature, but depending upon changes in the type of activity, food, exposure, muscle tone and other factors, which are imposed by a difference in climate and regimen.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Ahlmannryggen: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

H.U.Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Kirwanveggen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Neumayerskarvet: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

Determination of the Thickness of Ice Shelves by Seismic Shooting Methods - Robin, Gordon de Quetteville (Nature, 1956)
SEISMIC soundings of the thickness of the floating ice shelves of Antarctica have so far been attempted by two expeditions, the Second Byrd Antarctic Expedition of 1933–35 1, and the Norwegian–British–Swedish Antarctic Expedition 1949–52 2,3. Further measurements are likely to be made by several expeditions during the International Geophysical Year 1957–58. Reinterpretation of results from iceshelves obtained from the Norwegian-British-Swedish Antarctic expedition 1949-52.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Upper Air Temperatures over an Antarctic Station: A preliminary note by - Schumacher, Nils Jørgen (Tellus, 1955)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

Sledge dogs of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1954)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; sledehunder

Measurements of ice thickness in Dronning Maud Land - Robin, Gordon de Quetteville (Polar Record, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Landmålerliv i Dronning Maud Land - Roer, Nils (Brøggers forlag, 1954)
Keywords: Dronning Maud Land; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; kartografi; landmåling

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

The base of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An International Expedition to Antarctica - Robin, Gordon de Quetteville (The Geographical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Measurements of Ice thickness in Dronning Maud Land, Antarctica - Robin, Gordon de Quetteville (Nature, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; glasiologi

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Robin, Gordon de Quetteville (Polar Record, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Preliminary note on the geology of western Dronning Maud Land - Roots, Ernest Frederick (Brøggers forlag, 1953)
Keywords: Dronning Maud Land; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi

Mechanical Transport of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Swithinbank, Charles (Polar Record, 1953)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Antarktis, der snøfokket pisker i juli : om ismassene rundt Sydpolen smelter, stiger verdenshavene med 30 meter : "Norsel"-ekspedisjonen får stor betydning for vitenskapen - [Roer, Nils] (Nå, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsel (skip); Norsk-britisk-svenske antarktisekspedisjon; Sydpolen; vitenskap

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1951)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Die Norwegisch-Britisch-Schwedische Expedition in die Antarktis - Sverdrup, Harald Ulrik (Polarforschung, 1951)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The International Expedition to Queen Maud Land (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1950)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Roberts, Brian Birley (Polar Record, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Norwegian-British-Swedish Expedition to Queen Maud Land (The Geographical Journal, 1949)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

The Queen Maud Land Expedition (The Geographical Journal, 1949)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Preliminary Glaciological Plans for the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Ahlmann, Hans Wilhelmsson (Journal of Glaciology, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The Norwegian-Swedish-British Antarctic Expedition - Ahlmann, Hans Wilhelmsson (Tellus, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Antarctic Continent - Law, Phillip Garth (Walkabout, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Norwegian-British-Swedish expedition to the Antarctic (The Geographical Journal, 1948)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Norwegian-British-Swedish Expedition to the Antarctic (The Geographical Journal, 1948)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Proposed British-Norwegian-Swedish Antarctic Expedition, 1948–50 (Polar Record, 1947)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Contemporary International Interest in the Antarctic - Fleming, W L S (International Affairs, 1947)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon